Pola komunikasi digital pemerintah dalam menanamkan identitas nasional: Studi pada kampanye media sosial - Rasyadan, Muhammad Irfan (Maliki Interdisciplinary Journal, 2025)
National identity is the foundation of nationality that must be instilled adaptively in the digital era. The Indonesian government and several public figures have utilized social media as a strategic communication channel to convey national values. This study aims to analyze the digital communication patterns of the government in strengthening national identity through social media and to assess its effectiveness and challenges. The approach used is descriptive qualitative with literature study and content analysis methods on official government social media accounts and public figures such as Dedi Mulyadi. The results show that national symbols, local culture, and national narratives are the main elements in national identity campaigns, but they are not yet fully effective due to limited public participation and inconsistent messaging.